Developing EFL Learners’ Pragmatic Competence through a Blended Learning Model: A Quasi-Experimental Study - Mohamed Bouftira; Mohammed El Messaoudi; Shuai Li (European Scientific Journal, ESJ, 2022)
In the era of globalization, EFL (English as a Foreign Language) teachers have nominated to weld EFL instruction and aspects of intercultural competence together.  Howbeit, the literature on the topic promulgates that procuring pragmatic competence remains a high-priority quest for EFL learners worldwide. This paper delineates the use of a blended learning model to teach pragmatic competence in an EFL context. This quasi-experimental study sought to probe into the potential of a blended learning model on participants’ levels of pragmatic competence. 62 students from a junior high school participated in the study. 32 participants belonged to the control group and 30 participants belonged to the experimental group. The main findings demonstrated that the three-week blended learning model resulted in a statistically significant impact on participants’ levels of pragmatic competence; that is, the experimental group participants (M=16.40; SD=2.54) remarkably outperformed the control group participants (M=11.87; SD=3.49) on the posttest. This implies that foreign language teachers are highly encouraged to attach much importance to amalgamating classroom teaching and the use of interactive websites (blended learning) as a way to develop the pragmatic competence of language learners.